Natural pigments: innovative extraction technologies and their potential application in health and food industries - Ayu Masyita; Gemala Hardinasinta; Ayun Dwi Astuti; Firdayani Firdayani; Dian Mayasari; Aki Hori; Ira Nur Ainun Nisha; Firzan Nainu; Takayuki Kuraishi (Frontiers in Pharmacology)
Natural pigments, or natural colorants, are frequently utilized in the food industry due to their diverse functional and nutritional attributes. Beyond their color properties, these pigments possess several biological activities, including antioxidant, anti-inflammatory, anticancer, antibacterial, and neuroprotective effects, as well as benefits for eye health. This review aims to provide a timely overview of the potential of natural pigments in the pharmaceutical, medical, and food industries. Special emphasis is placed on emerging technologies for natural pigment extraction (thermal technologies, non-thermal technologies, and supercritical fluid extraction), their pharmacological effects, and their potential application in intelligent food packaging and as food colorants. Natural pigments show several pharmaceutical prospects. For example, delphinidin (30 µM) significantly inhibited the growth of three cancer cell lines (B16-F10, EO771, and RM1) by at least 90% after 48 h. Furthermore, as an antioxidant agent, fucoxanthin at the highest concentration (50 μg/mL) significantly increased the ratio of glutathione to glutathione disulfide (p < 0.05). In the food industry, natural pigments have been used to improve the nutritional value of food without significantly altering the sensory experience. Moreover, the use of natural pH-sensitive pigments as food freshness indicators in intelligent food packaging is a cutting-edge technological advancement. This innovation could provide useful information to consumers, increase shelf life, and assist in evaluating the quality of packaged food by observing color variations over time. However, the use of natural pigments presents certain challenges, particularly regarding their stability and higher production costs compared to synthetic pigments. This situation underscores the need for further investigation into alternative pigment sources and improved stabilization methods. The instability of these natural pigments emphasizes their tendency to degrade and change color when exposed to various external conditions, including light, oxygen, temperature fluctuations, pH levels, and interactions with other substances in the food matrix.